TRADE LIBERALISATION, MARKET POWER AND SCALE EFFICIENCY IN INDIAN INDUSTRY - Pulapre Balakrishnan Pushpangadan, K and Suresh Babu, M (Centre for Development Studies-WP336, 2002)
Using information on listed firms in each of the industry groups at the two-digit level within Manufacturing this study investigates whether the radical shift in trade policy in India in 1991 resulted in a reduction in market power and/or an improvement in scale efficiency. We estimate a group-wise production function allowing for firm-specific effects. A plausible estimate of market power is obtained and the assumption of constant returns to scale is mostly rejected. As regards the effects of the trade-policy shock of 1991, evidence of a move to a more competitive market structure or of an improvement in scale efficiency is not widespread across Indian manufacturing.